Diversity and knowledge of plants used in the treatment of snake bite envenomation in Benin - Dossou, Ayékotchami Jacques; Fandohan, Adandé Belarmain; Djossa, Agossou Bruno; Assogbadjo, Achille Ephrem (Ethnobotany Research and Applications, 2021)
Background: Ophidian envenomation is a public health problem in the tropics and subtropics. Expensive cost of antivenoms forces most of the population to resort to medicinal plants as a first-line treatment. The present study aimed to contribute to a better knowledge of medicinal plants used in the treatment of snakebite envenomation in Benin. Methods: Ethnobotanical information was collected from 339 people (hunters and traditional healers) across various sociolinguistic groups using a structured interview and the snowball technique. Knowledge was quantitatively assessed using the Relative Citation Frequency. The R software (cran.r-project.org) and Microsoft Excel were used to produce graphs and/or charts. Results: A total of 109 plants species belonging to 51 botanical families were reported as being used in the treatment of snakebite envenomation. Distribution of these species by family showed that Leguminosae (20.18%), Euphorbiaceae (9.17%), Asteraceae (4.59%), Annonaceae (3.67%) were mentioned the most. The dominant life forms were herbs and shrubs collected mainly from savannas and fallows. Roots and leaves were the most used plant parts in the preparation of remedies. Conclusion: In-depth pharmacological and toxicological studies must be carried out to validate reported medicinal plants, to contribute to the well-being of local communities in developing countries. Keywords: Ethnobotanical survey, ophidian envenomation, antivenom, medicinal plants, well-being.